An Empirical Research Agenda for the Forensic Sciences - Koehler, Jonathan J. (2016)
After the National Academy of Sciences issued a stunning report in 2009 on the unscientific state of many forensic science subfields, forensic science has undergone internal and external scrutiny that it had managed to avoid for decades. Although some reform efforts are underway, forensic science writ large has yet to embrace and settle upon an empirical research agenda that addresses knowledge gaps pertaining to the reliability of its methods. Our paper addresses this problem by proposing a preliminary set of fourteen empirical studies for the forensic sciences. Following a brief discussion of the courtroom treatment of forensic science evidence, we sketch a series of studies that should be conducted to increase understanding of what forensic examiners are doing, how accurately they are doing it, and how cognitive bias may affect the work product. We also propose several studies that examine how the specific questions examiners are asked might affect the validity and persuasiveness of examiners’ responses. We conclude by affirming the importance of developing a research culture within the forensic sciences that includes a commitment to conducting, participating in, and relying upon high quality empirical research